New directions in information organization - Park, Jung-ran; Howarth, Lynne Christine (Emerald, 2013)
New directions in information organization, co-edited by Dr. Jung-ran Park and Dr. Lynne Howarth seeks to provide an overview and understanding of the future directions, leading edge theories and models for research and practice in information organization.
Includes index.
Keywords: Information resources management.; elektronické knihy; electronic books